Role of diagnostic laparoscopy in infertility - Abhishek Kumar; Dr.Snehlata; Manjula Srivastava; R S Vandana (Surgical Review: International Journal of Surgery, Trauma and Orthopedics, 2020)
Background: Use of diagnostic and therapeutic laparoscopy in infertility has been a focus of attention in recent years and demonstrated to be very effective method in evaluating these cases. The main objective of the study was to detect the diagnostic efficacy of laparoscopy in uterine, pelvic and ovarian pathologies.Methods: This study was conducted from April 2017 to August2019.This prospective study included 50 infertile women and it was conducted at Vandana nursing home and IVF clinic. After thorough gynecological examination, necessary investigations were made and written consent form was taken from them before laparoscopy. The patients were kept fasting for 24 hours before the laparoscopy and the procedure was performed under general anaesthesia. All the data was collected on pre-designed proforma and the results were tabulated and raw percentages calculated to describe the results.Results: Among 50 patients, 36 were of primary infertility cases and 14 were of secondary infertility. In primary infertility maximum number of patients belonged to age group of 21-25 years where as secondary infertility was under the age group 26–30 years and above 31 years of age. Longest duration of infertility in primary was 16 years and that in secondary was 17 years. Out of 50 patients, 7 (14%) had absolutely normal laparoscopic findings. Among the various pathologies observed, tubal pathology contributed the most (44%), followed by ovarian (30%), pelvic (18%) and uterine (16%) pathologies.Conclusions: Laparoscopy is safe and cost-effective method and should be considered as prime diagnostic tool for evaluating the etiology of infertility in women and for effective treatment decisions.